Problems and prospects of management accounting improvement for innovation and investment activities in agricultural enterprises - V. Govdya, Viktor (2020)
The modern Russian agro-industrial facility, including its key manufacturing industry - agriculture, is characterized by a steady transition from a reproductive type of development to an innovative one aimed at labor productivity increase, an effective implementation of import substitution and exports increase state policy in respect of agro-industrial products. The competitive development of agricultural production, the need to solve a complex set of tasks immediately concerning a multiple increase of domestic agricultural product manufacture, primarily through the use of new biological assets, presupposes an exclusively innovative development of agriculture.It is clear that this situation is associated with the need to find new sources of investment, and to intensify the innovative activity of agricultural enterprises. In these conditions, it is extremely important to consider investment and innovation as a single, integral system, the success of which depends on the level of agricultural production competitiveness and sustainability. Of course, the organization of research work in this aspect requires an adequate understanding of innovations and innovative product content and role, the mechanism of innovation use during their creation.